Problem-Based Learning Worksheet for Grade 11 Biodiversity – Global Prestasi School - Afdan, Nikita Theresia (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2024)
The development of learning products in the form of worksheets aims to increase student engagement in learning. This research aims to develop a problem-based learning geography worksheet on the topic of biodiversity for 11th-grade students at SMA Global Prestasi. The research uses a research and development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). The researcher designed the product, validation instruments, and material analysis. The material analysis phase was conducted by media experts, subject matter experts, and learning practitioners. Data collection techniques used questionnaires and interviews with descriptive analysis. The validation test met the criteria for being highly valid with a score of 4. The student assessment met the criteria for being highly engaging with a score of 3.7. Based on these results, it can be concluded that problem-based learning worksheets can be used to enhance student engagement in learning geography.